Diurnal 24-Hour Rhythm in Ambulatory Heart Rate Variability during the Day Shift in Rotating Shift Workers. (June 2013) - Yoshizaki, Takahiro; Kawano, Yukari; Tada, Yuki; Hida, Azumi; Midorikawa, Toru; Hasegawa, Kohe; Mitani, Takeshi; Komatsu, Taiki; Togo, Fumiharu
Circadian variation in cardiac autonomic nervous system activity and behavior during the day shifts of shift workers has not hitherto been clarified. This study examined diurnal 24-h variation in heart rate variability (HRV), sleep-wake cycle, physical activity, and food intake during the day shift in rotating shift workers. The subjects were female nurses and caregivers working at a health care facility (14 day workers and 13 rotating shift workers). Each subject was asked to undergo 24-h electrocardiograph and step count recordings. Coarse graining spectral analysis was used for approximately 10-min segments of HRV (600 beats) to derive the total power (TOT: >0.04 Hz), integrated power in the low-frequency (LF: 0.04-0.15 Hz) and high-frequency (HF: >0.15 Hz) ranges, the ratio of HF power to TOT (HF nu), and the ratio of LF power to HF power (LF/HF). Double cosinor analysis was used to obtain 24-h and 12-h period variations in variables of HRV and physical activity. While no difference was found in the acrophases of either period for step counts or in the 12-h period of HRV variables between the groups, the acrophases of the 24-h period for HRV variables were delayed by 1.3 to 5.5 h in rotating shift workers, and their differences in HF power, HF nu, and LF/HF reached a significant level ( p < 0.05). On the days of the experiment, retiring time, waking up time, total time in bed, sleep efficiency, and mealtimes and energy intake for each diet did not differ between the groups. These results suggest that there is a possibility of an abnormal phase angle between circadian variation in cardiac autonomic nervous system activity and the sleep-wake cycle during the day shift in shift workers.